2015
DOI: 10.1016/j.ejcdt.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of thoracentesis in the management of tuberculous pleural effusion

Abstract: Background: Tuberculous pleural effusion (TPE) is the second most common form of extrapulmonary tuberculosis (EPTB). Up to 50% after treatment complicated with pleural thickening. Pleural biopsy has been considered the gold standard in diagnosis of TPE but it is invasive, so that pleural fluid markers of TPE have been extensively evaluated as an alternative to pleural biopsy. Thoracentesis for measuring these fluid markers is important.Aim: Assessing the value of diagnostic thoracentesis (by measuring pleural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…[12] Patients with TB-PLE tend to be younger than patients with P-TB. In one recent series from Qatar and Agha et al 2015, the mean age of 100 patients with TBP-E was 31.5 year, [13] thus, the age of patients in present study matched the age reported to be susceptible to tubercular pleurisy in previous series. [11] Significantly increased ADA activity in the serum of pulmonary TB and tubercular pleural effusion patients compared to healthy controls and non-TB pleural effusion is due to activation of cell mediated immunity (delayed hypersensitivity) to Mycobacterium tuberculosis antigen.…”
Section: Discussionsupporting
confidence: 79%
“…[12] Patients with TB-PLE tend to be younger than patients with P-TB. In one recent series from Qatar and Agha et al 2015, the mean age of 100 patients with TBP-E was 31.5 year, [13] thus, the age of patients in present study matched the age reported to be susceptible to tubercular pleurisy in previous series. [11] Significantly increased ADA activity in the serum of pulmonary TB and tubercular pleural effusion patients compared to healthy controls and non-TB pleural effusion is due to activation of cell mediated immunity (delayed hypersensitivity) to Mycobacterium tuberculosis antigen.…”
Section: Discussionsupporting
confidence: 79%
“…Severe inflammatory reaction secondary to TB results in residual pleural thickening. Previous several studies have demonstrated use of combined antituberculous treatment with pleural drainage in early stages to relieve dyspnoea and reduce residual pleural thickening 4–7. One other study reported use of intercostal pleural drainage as an inpatient for median 57 days to successfully treat tuberculous empyema 8…”
Section: Discussionmentioning
confidence: 99%
“…6 Another study showed thoracocentesis prevented the occurrence of pleural thickening, apart from being diagnostic and therapeutic. 7 Thus management of pleural TB involves four-drug regimen along with therapeutic thoracocentesis and the radiological resolution takes longer exists even after the required duration of treatment is completed.…”
Section: Expert Opinionmentioning
confidence: 99%